2016
DOI: 10.1016/j.nbd.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Axonal plasticity of age-defined dentate granule cells in a rat model of mesial temporal lobe epilepsy

Abstract: Dentate granule cell (DGC) mossy fiber sprouting (MFS) in mesial temporal lobe epilepsy (mTLE) is thought to underlie the creation of aberrant circuitry which promotes the generation or spread of spontaneous seizure activity. Understanding the extent to which populations of DGCs participate in this circuitry could help determine how it develops and potentially identify therapeutic targets for regulating aberrant network activity. In this study, we investigated how DGC birthdate influences participation in MFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
2
44
0
2
Order By: Relevance
“…5,23 We recently found that both early- and adult-born DGCs contribute to mossy fiber sprouting, 17 but it remains unclear whether these populations differ in the extent to which they receive mossy fiber innervation. We used the DGC marker Prox1 to quantify mCh+/Prox1+ (GFP-negative) cells, representing DGCs that monosynaptically innervate birthdated starter neurons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,23 We recently found that both early- and adult-born DGCs contribute to mossy fiber sprouting, 17 but it remains unclear whether these populations differ in the extent to which they receive mossy fiber innervation. We used the DGC marker Prox1 to quantify mCh+/Prox1+ (GFP-negative) cells, representing DGCs that monosynaptically innervate birthdated starter neurons.…”
Section: Resultsmentioning
confidence: 99%
“…15,17 Briefly, P7 pups were anesthetized on ice and placed on a neonatal rat stereotaxic adapter (Stoelting, Wood Dale, IL) in a Kopf stereotaxic frame (Tujunga, CA). Bilateral burr holes were drilled and 1 μL of RV-Syn-GTR was injected (0.1 μL/min) using a 5 μL Hamilton syringe with the following coordinates (in mm from bregma and mm below the skull): caudal 2.0, lateral 1.5, depth 2.7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian envelope glycoprotein subgroup A (EnvA)-pseudotyped RbV (RbV-mCh) was produced as described previously (Wickersham et al, 2010) with titers of 1–8 × 10 8 cfu/mL. We injected Syn-GTR bilaterally into the dorsal dentate gyrus at postnatal day (P) 7 as previously described (Althaus et al, 2016; Kron et al, 2010) to birthdate neonatally-born dentate granule cells and render them RbV-competent. For additional details, see Supplemental Information.…”
Section: Methodsmentioning
confidence: 99%
“…During the development of temporal lobe epilepsy, adult-generated dentate granule cells integrate abnormally into the hippocampus (Shapiro et al, 2007; Walter et al, 2007; Jessberger and Parent, 2015; Singh et al, 2016; Althaus et al, 2016). Abnormal granule cells are hypothesized to mediate epileptogenesis by impairing the “dentate gate”, a property of the hippocampal circuit that normally limits excess excitation (Krook-Magnuson et al, 2015; Scharfman and Bernstein, 2015).…”
Section: Introductionmentioning
confidence: 99%